Implementasi Media Audio Visual Terhadap Responsibilitas Peserta Didik pada Mata Pelajaran PAI: Penelitian di Kelas 5 SDN Bubulak 2 Kota Bogor - Mahesa Rana Kharisma; Indry Nirma Yunizul Pesha; Ahmad Mulyadi Kosim (At-Tadris: Journal of Islamic Education, 2025)
The implementation of audio visual media in PAI learning is more conducive, fun, and makes it easier for students to increase their responsibility as students. The background of this study: the phenomenon in the field can be seen in the low level of responsibility of students in grade 5 of SDN Bubulak 2 Bogor City. Therefore, media that can increase student responsibility is audio visual media. The focus of this research problem is the implementation of audio visual media in PAl subjects on student responsibility can be increased, supporting factors and inhibiting student responsibility in PAI learning by implementing audio visual media in grade 5 SDN Bubulak 2 Bogor City. This study aims to find out the implementation of Audio Visual media in PAI subjects in grade 5 SDN Bubulak 2 Bogor City, find out that the responsibility of students in grade 5 can be increased by implementing audio visual media in PAI subjects, find out the supporting factors and inhibiting of student responsibility in PAI learning by implementing audio visual media in grade 5 SDN Bubulak 2 Bogor City. This study uses a qualitative approach of descriptive analysis through interview and documentation data collection techniques. By using data reduction analysis, data presentation and conclusion. The results of the study show that in general the implementation of audio visual media has been carried out quite well, and has been attended by a total of 21 students. Based on the results of research at SDN Bubulak 2 Bogor City, it shows an increase in the responsibility of students in grade 5. Of all 21 students in PAl learning who experienced an increase in responsibility, 17 people experienced an increase in responsibility, while 4 people did not experience an increase in responsibility. Factors that support the responsibility of students in implementing audio visual media are good health, caring parents, motivating teachers, and a supportive environment. Meanwhile the inhibiting factors are from poor health, lack of parental attention, lack of motivation from teachers, lack of cooperation between the school and parents, and a less supportive environment. Student responsibility is seen from the role of teachers, parents, and the environment in increasing the responsibility of students at SDN Bubulak 2 Bogor City.